PENGEMBANGAN MODUL LARUTAN PENYANGGA BERBASIS PENDEKATAN TERPADU STEM - Amelia Tripripa; Hermansyah Amir; Salastri Rohiat (University of Bengkulu, 2020)
This study aims to determine the feasibility, student response and effectiveness of buffer solution modules based on the integrated STEM approach developed. This research is a development research adapted from the development model of Borg and Gall. The study was conducted in January - April 2019 at SMAN 09 Kota Bengkulu. The research data were obtained from the results of interviews, validation questionnaires, student response questionnaires and understanding tests. The selection of the trial class was carried out through a normality test for all class XI MIPA with a total subject of 111 students. The results of the trial were obtained by two respondent classes namely XI MIPA 1 for trial use and XI MIPA 2 for product testing with a total of 38 students. The results of the validation test obtained an average assessment of material experts 4.3 and 4.7 media experts who were both in the range of 4,2 ? < 5 with a very valid classification. In product testing and usage tests, the average score of students' responses was 4.3 with a very interesting classification. The effectiveness of the module is seen from the understanding test with the percentage of student learning completeness of 86.21% reaching the KKM which is categorized as effective. So it can be concluded that, in general, the module based on the solution based on the STEM approach developed can be used in the learning process in class XI MIPA SMAN 09 Kota Bengkulu in the academic year 2018/2019.